If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = -2 + -3n Solving 7 = -2 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. 7 + 3n = -2 + -3n + 3n Combine like terms: -3n + 3n = 0 7 + 3n = -2 + 0 7 + 3n = -2 Add '-7' to each side of the equation. 7 + -7 + 3n = -2 + -7 Combine like terms: 7 + -7 = 0 0 + 3n = -2 + -7 3n = -2 + -7 Combine like terms: -2 + -7 = -9 3n = -9 Divide each side by '3'. n = -3 Simplifying n = -3
| 22+8n=54 | | 20+7-4(x+1)= | | 2+7a+7=20+2a | | 10+3h=-6+2h | | -15x^2=12x-5 | | 3a+3b+2a= | | -17=a-3 | | 12x-12=8+6+6x | | m+4=6m-2 | | 2(2x+4)/2= | | -2=1+x | | 65X=31 | | 7+x=9+27 | | 1x+16=1x | | 5x+2(10x)+4(25x)=12.50 | | 11+5e=8+4e | | -6x+1=2x-7 | | 28-4d=-12-3p | | z+n=m | | (r-4)(r+1)+(r-4)(r+6)=0 | | 14+x=5+2x | | 3x^2+12x-64=0 | | 8.1-0.6x=7.2 | | 51+5x=24+8x | | y+23=45 | | -4*2r+-5=-44 | | 33+4x=49+2x | | y-t=-5 | | 3.4x=5 | | z+2=1 | | 3(4y-3)-(4y+4)= | | 71+2x=49+3x |